National Ambulatory Medical Care Survey, 1990 ([Verlag nicht ermittelbar], 1993)
The National Ambulatory Medical Care Surveys (NAMCS) supply data on ambulatory medical care provided in physicians' offices. The 1990 survey contains information from 43,469 patient visits to 1,684 physicians. Data are available on the patient's reason for the visit, the physician's diagnosis, and the kinds of diagnostic and therapeutic services rendered. Information is included on the physician's specialization and geographical location. Demographic information on patients, such as age, sex, race, and ethnicity, was also collected.